TikTok, Digital Da’wa and Religious Authorities - Muzayana (Universitas Muhammadiyah Yogyakarta, 2023)
This study explains the presence of da’wa influencers on social media. To narrow the discussion, the author takes a case study on TikTok social media. This study aims to determine whether new figures of da’wa on social media shift the old religious authority or traditional figures. The author describes this discussion using Heidi Campbell's digital religion concept approach. The author's analysis shows that these da’wa influencers do not claim to be scholars or religious scholars. The delivery of their da’wa is relaxed and not patronizing. The existence of this new da’wa figure belongs to the logic of continuity and complementarity, which means that their legitimacy is a form of continuity or as a successor of the old figure's authority.